Early and late complications of thyroidectomy: a descriptive cohort study in Rawalpindi - Sana Viqar; Ayesha Masood; Naeem Zia (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the epidemiology of thyroid disorders and early and late complications following thyroidectomy. Method: The descriptive cohort study was conducted at the Benazir Bhutto Hospital. Rawalpindi, Pakistan, from April 2017 to Janurary 2020, and comprised patients undergoing total and near-total thyroidectomy. Post-operative complications were noted, and patients were followed up at 6 months to assess long-term complications. Data was analysed using SPSS 22. Results: Of the 75 patients, 70(93.3%) were females and 43(58.1%) were aged <40 years. The most common symptom was neck swelling with hyperthyroidism 20(41.7%) and pressure symptom 20(41.7%). Post-operative complications developed in 26(35.6%), with symptomatic hypocalcaemia being the most common 10(13.7%), followed by hoarseness 6(8.2%). Biopsy results were available for 50(66.6%) patients. Benign pathology was present in 44(88%) patients and 6(12.0%) had malignancy. Follow-up data was available for 62(82.7%) patients among whom symptomatic hypocalcaemia was the leading complication 33(53.2%), followed by permanent hoarseness 6(9.7%). Conclusion: Symptomatic hypocalcaemia and hoarseness were found to be the most common post-operative and long-term complications of thyroidectomy. Key Words: Thyroidectomy, Hypocalcaemia, Hoarseness, Complications, Malignancy.